2004
DOI: 10.1111/j.0300-9475.2004.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of C‐Type Lectin Natural Killer Receptor‐Like Loci in the Bony Fish Oreochromis niloticus

Abstract: The genome of the cichlid (teleost) fish Oreochromis niloticus contains a set of genes which encode group V C-type lectin proteins homologous to the mammalian NKG2/CD94 family of natural killer (NK) cell receptors. To determine the genomic organization of these killer cell-like receptor (KLR) genes, an O. niloticus BAC library was screened with a cDNA probe derived previously from an expressed sequence tag of the related cichlid species Paralabidochromis chilotes. Four distinct KLR-bearing BAC clones were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…While these genes encode an Ig domain, there is a cluster of C-type lectins encoded within this larger cluster [103,104]. Another bony fish, Oreochromis niloticus, possesses a KLR region, containing 26 genes, though more compact than its human counterpart [105]. Other teleosts have NKC genes, including Paralabidochromis chilotes [106] and rainbow trout [107], demonstrating that some of these genes arose in an ancestor common to both humans and bony fish earlier in the gnathostome lineage.…”
Section: Nk Receptor Gene Complexes In Other Speciesmentioning
confidence: 99%
“…While these genes encode an Ig domain, there is a cluster of C-type lectins encoded within this larger cluster [103,104]. Another bony fish, Oreochromis niloticus, possesses a KLR region, containing 26 genes, though more compact than its human counterpart [105]. Other teleosts have NKC genes, including Paralabidochromis chilotes [106] and rainbow trout [107], demonstrating that some of these genes arose in an ancestor common to both humans and bony fish earlier in the gnathostome lineage.…”
Section: Nk Receptor Gene Complexes In Other Speciesmentioning
confidence: 99%
“…On the genetic level the putative sequence of the so called NK cell enhancing factor (NKEF) has been sequenced in rainbow trout [46] and common carp [47]. Recently, sequences encoding group V C-type lectin homologous to the mammalian NKG2/CD94 family of NK cell receptors have been discovered in cichlid fishes [48,49]. In mammals, NKG2 receptors costimulate multiple NK activation receptors [50].…”
Section: Non-specific Cmcmentioning
confidence: 99%
“…Though not shown experimentally, one might speculate that cKLR sequences are expressed by killer cells in organs of the fish where innate immune effector function(s) are needed. As with CD94/NKG2 sequences in mammalian species, cKLR genes are also clustered in a narrow genomic NKC-like region [16, 17]. Altogether, there is substantial evidence indicating clustered NKR genes and gene families are an important genomic component retained in a diverse range of vertebrate species.…”
Section: Nk Receptors Polymorphisms and Specificitymentioning
confidence: 99%
“…Direct sequencing of BAC clones containing cKLR sequences further revealed that the CD94/NKG2-related gene sequences are clustered together in the cichlid fish genome [17]. Though related sequences have so far remained elusive in the trout, genetic mapping strategies based on an NK-like trait (i.e.…”
Section: The Nk Gene Complex (Nkc): Clustered Klr Genes Promote Namentioning
confidence: 99%
See 1 more Smart Citation